Distinguishing complicated from uncomplicated parapneumonic effusions. Issue 4 (July 2015) - Porcel, José M.
<x xml:space="preserve">Abstract</x> Purpose of review Treatment of parapneumonic effusions (PPEs) is challenged by the decision of whether or not to insert chest tubes. This review focuses on the factors that may aid in determining which patients require an immediate drainage of the pleural space, that is, have a complicated PPE. Recent findings Clinical guidelines advocate the evaluation of radiological (large effusion or loculation), bacteriological (Gram-positive stain or culture), biochemical (pH < 7.20 or glucose <60 mg/dl), and macroscopic (pus) characteristics of the pleural fluid to assist in the identification of complicated PPEs. In the past few years, a number of new pleural fluid biomarkers have been tested for the same purpose, but with the exception of C-reactive protein (CRP), they should be considered investigative. A pleural fluid CRP higher than 100 mg/l or a serum CRP higher than 200 mg/l, when combined with pleural fluid pH or glucose, may greatly increase our capability to predict the need for instituting tube thoracostomy. Although some ultrasonographic and computed tomography features favor the diagnosis of pleural infection, their role in uncomplicated–complicated PPE discrimination has not been systematically evaluated. Summary No pleural fluid tests, other than pH or glucose, have gained wide acceptance for the assessment of patients with PPE. However, if corroborated with further studies, the measurement of pleural fluid or serum CRP, in combination with the classical fluid parameters, may have the potential to be incorporated into medical decision making.